Post‐fragmentation population structure in a cooperative breeding Afrotropical cloud forest bird: emergence of a source‐sink population network. Issue 6 (6th March 2015) - Husemann, M.; Cousseau, L.; Callens, T.; Matthysen, E.; Vangestel, C.; Hallmann, C.; Lens, L.
Abstract: The impact of demographic parameters on the genetic population structure and viability of organisms is a long‐standing issue in the study of fragmented populations. Demographic and genetic tools are now readily available to estimate census and effective population sizes and migration and gene flow rates with increasing precision. Here we analysed the demography and genetic population structure over a recent 15‐year time span in five remnant populations of Cabanis's greenbul ( Phyllastrephus cabanisi ), a cooperative breeding bird in a severely fragmented cloud forest habitat. Contrary to our expectation, genetic admixture and effective population sizes slightly increased, rather than decreased between our two sampling periods. In spite of small effective population sizes in tiny forest remnants, none of the populations showed evidence of a recent population bottleneck. Approximate Bayesian modelling, however, suggested that differentiation of the populations coincided at least partially with an episode of habitat fragmentation. The ratio of meta‐Ne to meta‐Nc was relatively low for birds, which is expected for cooperative breeding species, while Ne /Nc ratios strongly varied among local populations. While the overall trend of increasing population sizes and genetic admixture may suggest that Cabanis's greenbuls increasingly cope with fragmentation, the time period over which these trends were documented is rather short relative to the average longevity of tropical species. Furthermore, the critically low Nc in the small forest remnants keep the species prone to demographic and environmental stochasticity, and it remains open if, and to what extent, its cooperative breeding behaviour helps to buffer such effects.